Horizontal Eye Position Affects Measured Vertical VOR Gain on the Video Head Impulse Test - McGarvie, Leigh A.; Martinez-Lopez, Marta; Burgess, Ann M.; MacDougall, Hamish G.; Curthoys, Ian S. (Frontiers in Neurology, 2015)
Background/hypothesis: With the video head impulse test (vHIT), the vertical VOR gain is defined as (vertical eye velocity/vertical head velocity), but compensatory eye movements to vertical canal stimulation usually have a torsional component. To minimize the contribution of torsion to the eye movement measurement, the horizontal gaze direction should be directed 40° from straight ahead so it is in the plane of the stimulated canal plane pair. Hypothesis: as gaze is systematically moved horizontally away from canal plane alignment, the measured vertical VOR gain should decrease. Study design: Ten healthy subjects, with vHIT measuring vertical eye movement to head impulses in the plane of the left anterior-right posterior (LARP) canal plane, with gaze at one of five horizontal gaze positions [40°(aligned with the LARP plane), 20°, 0°, −20°, −40°]. Methods: Every head impulse was in the LARP plane. The compensatory eye movement was measured by the vHIT prototype system. The one operator delivered every impulse. Results: The canal stimulus remained identical across trials, but the measured vertical VOR gain decreased as horizontal gaze angle was shifted away from alignment with the LARP canal plane. Conclusion: In measuring vertical VOR gain with vHIT the horizontal gaze angle should be aligned with the canal plane under test.